Roflumilast Attenuates Doxorubicin-Induced Cardiotoxicity by Targeting Inflammation and Cellular Senescence in Cardiomyocytes Mediated by SIRT1 - Zhang S; Wu P; Liu J; Du Y; Yang Z (Dove Medical Press, 2021)
Sheng Zhang,1,2 Peng Wu,1 Jiabao Liu,1 Yingqiang Du,1 Zhijian Yang1 1Department of Cardiology, The First Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu 210029, People’s Republic of China; 2Department of Cardiology, The Third Affiliated Hospital of Soochow University, Changzhou, Jiangsu 213004, People’s Republic of ChinaCorrespondence: Zhijian YangDepartment of Cardiology, The First Affiliated Hospital of Nanjing Medical University, No. 300, Guangzhou Road, Gulou District, Nanjing, Jiangsu, 210029, People’s Republic of ChinaTel/Fax +86-25-52271000Email yangzhijian173@163.comBackground and Purpose: Cardiotoxicity is an important side effect of the treatment of a malignant tumor with Doxorubicin. Currently, decreasing the dosage of Doxorubicin to alleviate the side effects on cardiac function is the common method to deal with the cardiotoxicity induced by Doxorubicin. The present study aims to investigate the therapeutic effects of Roflumilast on Doxorubicin-induced inflammation and cellular senescence, as well as the potential mechanism in H9c2 myocardial cells.Methods: The injured cardiac cell model was established by incubation with 5 μmol/L Doxorubicin. MTT was used to evaluate the cell viability of treated H9c2 cardiac cells. The expression of 4-HNE was determined using an immunofluorescence assay. The gene expression levels of IL-17, IL-6, TNF-α, IL-4, PAI-1, p21, and SIRT1 were evaluated using qRT-PCR and the protein levels of Gpx4, PAI-1, p21, and SIRT1 were determined using Western blot analysis. Secretions of IL-17, IL-6, TNF-α, IL-4, CK-MB, and cTnI were measured using ELISA. Cellular senescence was assessed using SA-β-Gal staining. Si-RNA technology was used to knockdown the expression of SIRT1 in H9c2 cardiac cells.Results: Cell viability of H9c2 cardiac cells was significantly inhibited by Doxorubicin but rescued by Roflumilast. The upregulated 4-HNE and downregulated Gpx4 were reversed by Roflumilast. The secretions of IL-6 and IL-17 were promoted by Doxorubicin and suppressed by Roflumilast. The increased SA-β-Gal staining induced by Doxorubicin was inhibited by Roflumilast. P21 and PAI-1 were significantly upregulated and SIRT1 was greatly downregulated by Doxorubicin, all of which were reversed by Roflumilast. The anti-senescent effect of Roflumilast was abolished by knocking down SIRT1.Conclusion: Roflumilast might attenuate Doxorubicin-induced inflammation and cellular senescence in cardiomyocytes by upregulating SIRT1.Keywords: roflumilast, doxorubicin, SIRT1, cellular senescence, chronic heart failure